WORK SAFETY AND HEALTH AND DISCIPLINE IN AFFECTING EMPLOYEE WORK PRODUCTIVITY IN PT. TRI KEESON UTAMA GARUT - Wufron W (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2019)
PT. Tri Keeson Utama Garut is a company engaged in chocolate industry. This study aimed to determine the effect of work safety and health and discipline on employees’ work productivity. The problem in this study wasthe achievement of unattainable production targets that wereexpected to occur due to work safety and health and discipline. This research wasa quantitative research. The author conducteddata collection through instruments in the form of questionnaires containing statements and distributed them to 50 respondents as a sample of all members of the population in the production section. The instruments made werethen tested through validity and reliability testing. The analysis of the data used in this study wasmultiple regression analysis to test and prove the hypothesis. From the results of the research,work safety and healthhada partial influence on employees’ work productivity.Discipline also had an influence on employees’ productivity at PT. Tri Keeson Utama Garut, andwork safety and health and discipline simultaneously hada significant effect on employees’ work productivity at PT. Tri Keeson Utama Garut.